Analysis of the Content of Tiktok Comments @Dictionarei in A DAY WITH REI PART 350/ SWISS DAY - Kusumarini, Cahyawati Diah; Kuncoroyakti, Yohanes Arie; Rahella, Lucky Khairulisa (Lentera Ilmu Nusantara, 2024)
This research uses a qualitative content analysis method with a constructivistic paradigm, with new media theory as its basis. The data collected for this study were 80 randomly selected relevant comments on Tiktok social media regarding their opinions on the video post